(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the issues of animal husbandry, poultry farming, poultry farms, etc. the role of green algae - chlorella - in the development of a number of Sox, as well as in increasing soil fertility, in the absence of toxic chemicals, in the prevention of pests is extremely great, as well. the advantages of an inexhaustible source are highlighted.